Mental Health Conditions and Coping Strategies In Women With HIV and AIDS: A Systematic Review - Brigita Maria Karouw; Nursalam Nursalam; Saadah Saadah; Hilwatus Saadah; Stefanus Evan Rafael; Agrista Yudistira Purnama; Elizabeth Risha Murlina (STRADA : Jurnal Ilmiah Kesehatan, 2021)
In terms of mental health, people who know that they have AIDS will experience prolonged mental suffering. Purpose: This systematic study aims to review the mental health conditions in women with HIV/AIDS and how coping strategies are used. This systematic study has inclusion criteria, namely women with HIV/AIDS, where the articles used in English and Indonesian from 2015 to 2020, were carried out a systematic review using five databases (Scopus, Proquest, Science Direct, CINAHL, and Pubmed). Articles are written systematically based on the PRISMA protocol. The review results showed that women with HIV use coping focused on emotional problems and strategies. Various changes were experienced by women with HIV/AIDS. One of which can cause mental health problems. Implementing coping strategies will reduce anxiety and improve mental health